1999
DOI: 10.1021/jm9903949
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors. 16. 6,5,6-Tricyclic Benzothieno[3,2-d]pyrimidines and Pyrimido[5,4-b]- and -[4,5-b]indoles as Potent Inhibitors of the Epidermal Growth Factor Receptor Tyrosine Kinase

Abstract: Several elaborations of the fundamental anilinopyrimidine pharmacophore have been reported as potent and selective inhibitors of the epidermal growth factor receptor (EGFr) tyrosine kinase. This paper reports on a series of inhibitors whereby some 6,5-bicyclic heteroaromatic systems were fused through their C-2 and C-3 positions to this anilinopyrimidine pharmacophore. Although the resulting tricycles did not produce the enormous potency of some of the (5/6),6,6-bicyclic systems, the best of them had IC(50)s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…1,4,11) In this context, Showalter et al reported that fusing a third ring to 6-and 7-positions of the quinazoline ring enhanced the kinase inhibitory activity over the parent bicyclic analogues.…”
Section: 4)mentioning
confidence: 99%
See 2 more Smart Citations
“…1,4,11) In this context, Showalter et al reported that fusing a third ring to 6-and 7-positions of the quinazoline ring enhanced the kinase inhibitory activity over the parent bicyclic analogues.…”
Section: 4)mentioning
confidence: 99%
“…8,9) Consistent with this, some investigations showed that the isosteric replacement of the benzene ring of the quinazoline core with five-membered heteroaromatic rings is favorable. 10,11) The flexibility of the linking NH group between the heteroaryl core and the aniline ring permits the proper orientation of the aniline ring into the hydrophobic pocket, lying in the back of the ATP-binding site. 1) This hydrophobic pocket, often called "specificity pocket," is characteristic for each type of kinases, allowing for the design of selective ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tricyclic fragments 2 to 4 and compounds containing these pharmacophores also showed good LUDI scores of 411, 389, and 416, respectively. These three fragments have also been reported as potential kinase inhibitor scaffolds (24,34,35); however, their utility as components of an Aurora kinase inhibitor has not been reported. Therefore, compounds derived from these adeno-mimetic pharmacophores were of great interest to us for further development as Aurora kinase inhibitors.…”
Section: Fragment-based Virtual Screening Chemical Synthesis and Evmentioning
confidence: 99%
“…Fragments 1 to 4 were prepared using conditions described in the literature (23,24). The fragments were further converted to chloro derivatives by either using Vilsmeier's reagent (oxalyl chloride/DMF) or reacting with neat POCl 3 in the presence of 1,4-dioxane to make them more amenable to further chemical modification.…”
Section: Fragment-based Virtual Screening Chemical Synthesis and Evmentioning
confidence: 99%